The Study of the New Testament : a A Comprehensive Introduction - Piñero, Antonio, (Tools for Biblical Study ;, 2000)
The most thorough grounding available in the various disciplines of NT study, this is an invaluable tool for students, scholars and other serious readers of the earliest Christian writings. With a full survey of scholarship on each topic, in 600 packed pages the volume gives a reliable, in-depth presentation of: the history of interpretation - the NT canon - text criticism - the language of the NT - the historical and literary context - methods and approaches.